Treponema pallidum Rapid Test Screening Results Among Laboring Women: Associations With Parity and Gestational Age at Delivery - Firel Ferliandy Jabiy; Muh. Syafri Busra; Hamdiah Ahmar; Rachmawati Abdul Hafid; Tuti Sukini (Utan Kayu Publishing, 2026)
Syphilis during pregnancy can cause vertical transmission and adverse perinatal outcomes when not detected and treated early. The Treponema pallidum Rapid Test (TP Rapid) is used for syphilis screening within the Triple Elimination Program, particularly among pregnant and laboring women with unclear antenatal screening status. This study aimed to examine the association of parity and gestational age at delivery with TP Rapid screening results among laboring women at Sele Be Solu Regional Hospital, Sorong City, in 2024. This analytic observational study used a cross-sectional design and secondary data from medical records, delivery registers, and laboratory registers. A total of 762 laboring women were included through total sampling. Data were analyzed using univariate and bivariate analyses, including the Chi-square test and measures of association. Reactive TP Rapid results were found in 148 women (19.4%), whereas 614 women (80.6%) had nonreactive results. Parity was not significantly associated with TP Rapid results (p = 0.459). However, reactive TP Rapid results were more frequent in preterm than non-preterm deliveries (PR = 2.36; 95% CI: 1.78–3.12; OR = 3.09; 95% CI: 2.10–4.55; p < 0.001). Because TP Rapid is a treponemal screening test and this study used a cross-sectional design, reactive results should not be interpreted as active syphilis or causal evidence for preterm birth. Universal syphilis screening, confirmatory testing, treatment, newborn evaluation, and strengthened medical record documentation are recommended.